Pro Web 2. 0 Application Development with GWT - Dwyer, Jeff (New York : Apress L. P., 2008)
Annotation The main focus ofPro Web 2.0 Application Development with GWTis an analysis of a full-fledged Web 2.0 application called GWT College Bound. This book is for people who are looking to get beyond small proof-of-concept sample applications and want to see what the guts of a full-fledged Google Web Toolkit application should look like.
Trade